(untitled) (Botanica Orientalis: Journal of Plant Science, 2025)
Dust pollution is a major problem in cities of developing countries. The foliar surface of plants serves as a continual interface with the surrounding atmosphere, making it the primary recipient of dust particles. This inherent characteristic allows for assessing the ambient dust levels and the capacity of various plant species to intercept and alleviate it. This study aimed to investigate the efficiency of dust deposition among common roadside plant species and its effects on leaf biochemical properties, including pH, relative water content, and total chlorophyll content. Among the plant species studied, Malvaviscus arboreus exhibited the highest dust deposition on its leaf surface, while Pyrostegia venusta showed the lowest. The results revealed that the maximum dust deposition occurred during the post-monsoon season compared to the pre-monsoon season in all plant species. Dust deposition demonstrated significant positive correlations with relative water and ascorbic acid content, while its relationships with total chlorophyll levels and leaf extract pH were negative. This study suggests that certain roadside plant species can tolerate higher levels of dust pollution and thus can serve as effective natural filters, contributing to the mitigation of dust pollution in urban environments.